Psychosocial consequences of living kidney donation: a prospective multicentre study on health-related quality of life, donor–recipient relationships and regret. Issue 6 (13th December 2018) - Wirken, Lieke; van Middendorp, Henriët; Hooghof, Christina W; Sanders, Jan-Stephan F; Dam, Ruth E; van der Pant, Karlijn A M I; Wierdsma, Judith M; Wellink, Hiske; van Duijnhoven, Elly M; Hoitsma, Andries J; Hilbrands, Luuk B; Evers, Andrea W M
Abstract: Background: Previous studies have indicated decreased health-related quality of life (HRQoL) shortly after kidney donation, returning to baseline in the longer term. However, a subgroup of donors experiences persistent HRQoL problems. To identify which HRQoL aspects are impacted most by the donation and to identify at-risk donors, more specific insight into psychosocial donation consequences is needed. Methods: The current study examined the HRQoL course, donor-perceived consequences of donation for donors, recipients and donor–recipient relationships, and regret up to 12 months post-donation in donors from seven Dutch transplantation centres. Kidney donor candidates ( n  = 588) completed self-report questionnaires early in the screening procedure, of which 361 (61%) donated their kidney. Results: Data for 230 donors (64%) with complete assessments before donation and 6 and 12 months post-donation were analysed. Results indicated that donor physical HRQoL was comparable at all time points, except for an increase in fatigue that lasted up to 12 months post-donation. Mental HRQoL decreased at 6 months post-donation, but returned to baseline at 12 months. Donors reported large improvements in recipient's functioning and a smaller influence of the recipient's kidney disease or transplantation on the donor's life over time. A subgroup experienced negative donation consequences with 14% experiencing regret 12 months post-donation. Predictors of regret were more negative health perceptions and worse social functioning 6 months post-donation. The strongest baseline predictors of higher fatigue levels after donation were more pre-donation fatigue, worse general physical functioning and a younger age. Conclusions: Future research should examine predictors of HRQoL after donation to improve screening and to provide potential interventions in at-risk donors.